Gaya Kepemimpinan Kepala Sekolah Di SMP Negeri 3 Kota Tangerang Selatan - Nidatu Rifdah; Nadjematul Faizah (Fakultas Tarbiyah Institut Ilmu Al-Qur'an (IIQ) Jakarta, Indonesia, 2019)
This research was conducted to determine the principal's leadership style and to determine the requirements, duties and functions of the principal. In the last three years his has concurrently served as the Principal in SMP N 2 Kota Tangerang Selatan, but with him concurrently the position is not an obstacle and obstacle in carrying out his duties as headmaster in both schools. This research was conducted at SMP Negeri 3 Kota Tangerang Selatan. With the aim to find out the principal's leadership style in SMP Negeri 3 Tangerang Selatan. The research that the author uses is qualitative research, with a descriptive approach. This is because the researchers will describe or present a complete picture of the Principal's Leadership Style at SMP Negeri 03 Tangerang Selatan Selatan, to see how the leadership style of the SMP Negeri 03 Negri South Tangerang school leadership. The results of this study indicate that the leadership style used by principals in SMP Negeri 3 Kota Tangerang Selatan tends to the Democratic leadership style. Can be seen when solving problems and making decisions is good, very responsible in solving problems and always done by deliberation. The headmaster of SMP Negeri 3 Kota Tangerang Selatan in mobilizing / leading subordinates (staff, teachers and students) is to provide direct guidance such as guiding, motivating and giving direction to the subordinates concerned.